Klasifikasi Penjurusan pada Sekolah Menengah Atas (SMA) dengan Metode Algoritma C4.5 - Yofhanda Septi Eirlangga; Aldo Eko Syaputra (SEULANGA SYSTEM PUBLISHER, 2022)
The Indonesian Minister of Education has stipulated 12 years of compulsory education, but only at high school (SMA) students can only determine the major they are interested in. In every new academic year the PPDB (New Student Admissions) committee has difficulty in determining majors because the determination of majors is still done manually so that there is a mismatch with the interests and talents of students caused by human error. So it is necessary to conduct a study with the aim of assisting the PPDB committee in determining the majors accurately and effectively so that the interests and talents of students can be channeled appropriately. Therefore, the C4.5 algorithm method is used which is one of the data mining algorithms that produces a decision tree that is suitable for classifying large amounts of data. The data used in this study were taken from the grade IX student report cards in 2022 as many as 44 report cards which have 11 subject value variables, namely Science, Social Sciences, Indonesian Language, PKN, Islamic Religious Education, MTK, English, BAM Arts and Culture, ICT and Physical Education. The results of this study obtained a decision tree (decision tree) with 17 rules (knowledge) that has been matched with real data with a very high level of accuracy. So that this research can help and become a benchmark for the PPDB committee in determining the majors of new students every time a new teaching begins at SMA Pertiwi 2 Padang